Analysing French Teacher Communities Producing Online Resources: Perspectives on teacher agency - Baron, Georges-Louis; Zablot, Solène (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2025)
Online resources have become an important reality in education, accompanied by the phenomenon of the production, modification, and wide dissemination of educational resources by communities of teachers. This article explores the situation in France. First, we recall previous research on how teachers cooperate in order to create online resources. We distinguish between several types of collectives (captive communities, activist communities, proto-communities) and focus on their dynamics. Doing so implies considering the subjects as well as the instruments used and the social systems within which they evolve. Second, the issue of teacher agency relative to educational resources is analysed. In France, teachers are granted great freedom of pedagogical methods, a freedom not seen in all countries. Therefore, we analyse the activities of these collectives to understand how they view their activity and their role, specifically when using learning materials in class. An important related issue is the eagerness of administration to rely on evidence-based practice for orienting teacher action. We suggest that participatory research is a good investment for raising meaningful issues and proposing possible, short-term solutions.